The Role of Financial Literacy and Technology savviness on Fintech Adoption in Traditional Banking, the Mediating Role of Trust in Technology - Abbas, Naveed; Khan, Hafiz Gohar Mehmood (Pakistan Journal of Humanities and Social Sciences, 2024)
This study explores the drivers of fintech adoption, such as financial literacy and technological savviness, considering trust in technology as the moderating variable. Based on a quantitative analysis conducted on survey data related to users of both fintech and traditional banking in Pakistan, this research determines that financial literacy and technological savviness are statistically significant and positively influencing Fintech adoption. The role of trust in technology as a moderator is also substantial, showing the nuances involved in its influence on adoption. These results bring the need for financial and technological education and user-friendly fintech solutions to promote further financial inclusion toward an active digital financial ecosystem. These findings suggest that policymakers and fintech developers should increase efforts toward digital literacy improvement, the accessibility of platforms, and trust through increased data security to ensure that fintech services are indeed adopted in the long run.